Romania - Functional Review : Center of government - Evans, Gord (Washington, DC, 2013)
The medium-term objective of this review of the Center of Government (CoG) is to improve the Government's policy performance by strengthening Romania's policy process and policy institutions. The objective of the review will be accomplished by identifying short- and medium-term measures to strengthen central capacity to deliver high quality policy management to the Prime Minister and government and effectively coordinate policy with other central institutions and line ministries. Four critical success factors will signal effective implementation: 1. Decision makers will focus increasingly on strategic rather than legal or administrative issues; 2. Sound policy formulation will precede and guide legal drafting; 3. GSG will be empowered by the Prime Minister to enforce the rules and assure the quality of ministry proposals; and 4. The central institutions responsible for public policy and public finance management will work collaboratively to provide coherent, high quality support to the GoR. 2. The CoG review seeks to engage Romania's decision makers in these deliberations and, ultimately, in a concerted effort to improve Romania's policy performance.